The Effectiveness of Interactive Videos in Increasing Student Engagement in Online Learning - Haerawan Haerawan; Woolnough Cale; Uwe Barroso (Yayasan Adra Karima Hubbi, 2024)
The shift towards online learning has highlighted the need for innovative approaches to maintain student engagement. Traditional video lectures often fail to captivate students, decreasing attention and learning outcomes. Interactive videos incorporating quizzes, clickable hotspots, and branching scenarios have emerged as a potential solution to this challenge. This study aimed to evaluate the effectiveness of interactive videos in increasing student engagement in online learning environments compared to traditional video lectures. Additionally, it sought to identify the most impactful interactive elements and their correlation with learning outcomes. A mixed-methods approach was employed, involving 200 undergraduate students from diverse disciplines. Participants were randomly assigned to either an experimental group using interactive videos or a control group using traditional video lectures for a 6-week online course. Data collection methods included pre-and post-tests, engagement metrics (time spent, interaction frequency), and qualitative feedback through surveys and focus group discussions. Results demonstrated a significant increase in student engagement for the interactive video group, with 45% higher interaction rates and 30% longer viewing times than the control group. Quiz-based interactions and branching scenarios were found to be the most effective elements. Moreover, the experimental group showed a 25% improvement in learning outcomes as measured by post-test scores. In conclusion, this study provides strong evidence for the efficacy of interactive videos in enhancing student engagement and learning outcomes in online education. These findings suggest that incorporating interactive elements into video content can significantly improve the online learning experience, offering educators a valuable tool to address engagement challenges in digital learning environments.